Beneficial Diets and Pancreatic Cancer: Molecular Mechanisms and Clinical Practice - Zhang, Yang; Zhang, Tao; Yang, Wenbo; Chen, Hongze; Geng, Xinglong; Li, Guanqun; Chen, Hua; Wang, Yongwei; Li, Le; Sun, Bei (Frontiers in Oncology, 2021)
Pancreatic cancer (PC) is a malignant tumor with high invasiveness, easy metastatic ability, and chemoresistance. Patients with PC have an extremely low survival rate due to the difficulty in early diagnosis. It is estimated that nearly 90% of PC cases are caused by environmental risk factors. Approximately 50% of PC cases are induced by an unhealthy diet, which can be avoided. Given this large attribution to diet, numerous studies have assessed the relationship between various dietary factors and PC. This article reviews three beneficial diets: a ketogenic diet (KD), a Mediterranean diet (MD), and a low-sugar diet. Their composition and impact mechanism are summarized and discussed. The associations between these three diets and PC were analyzed, and we aimed to provide more help and new insights for the prevention and treatment of PC.